Prevalence of Osteoporosis and Osteopenia Status among Nepalese Population using Calcaneal Ultrasonography Method - Bagudai, Satyajit; Upadhayay, Hari Prasad (Journal of College of Medical Sciences-Nepal, 2019)
Background: A recent worldwide upsurge in the fracture incidence due to osteoporosis has underlined this underdiagnosed and undertreated condition. An awareness regarding the preventive, curative and rehabilitative care as well as a proper health policy is the need of hour. This requires a proper database of prevalence rate. This study aimed to find out the prevalence of osteoporosis and osteopenia by screening the bone health status in an apparently healthy population of Nepal. Methods: A cross sectional study was conducted among 465 apparently healthy subjects of either gender in three tertiary care health centers of Nepal for bone mineral density measurement by calcaneal ultrasonography. Results: The mean+SD of age among 465 patients was 45.47+14 years, including 43.2 % male and 56.8 % females. The prevalence of osteoporosis andosteopenia was 22.4% and 60.6% respectively. Our finding showed that prevalence of osteoporosis increases with age among either gender. Conclusions: The prevalence of osteoporosis in Nepalese population was high in comparison to other countries. There is no significant association of osteoporosis with females in comparison to males. The prevalence was increasing with age in either gender. These findings will help in creating a proper database of this condition in Nepal, helping the population,physicians as well as policy makers to have a proper address to this global emerging health problem.